PENERAPAN PROBLEM BASED LEARNING DENGAN MEDIA SCRAPBOOK UNTUK MENINGKATKAN HASIL BELAJAR - Laila Lutfiana; Muhammad Aunur Rofiq; Fulusia Nurmawati (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This classroom action research was initiated to optimize IPAS academic outcomes, teaching competencies, and student engagement inside grade IV at SDN 2 Pelem, specifically focusing on the theme "Daerahku Kaya Sumber Daya." The intervention integrated the Problem-Based Learning (PBL) framework coupled with scrapbook media. Initially, the study was triggered by substandard student academic performance, evidenced by a pre-cycle baseline mastery of only 21.05%. Following the Kemmis and McTaggart framework, the investigation spanned two successive cycles, each encompassing systematic phases of planning, acting, observing, and reflecting. A cohort of 19 fourth-grade students served as the research subjects. To gather comprehensive data, evaluation tests, direct observation logs, interviews, and documentation were utilized. The empirical findings demonstrated a progressive upward trend in learning mastery, expanding from the initial 21.05% to 63.16% during Cycle I, and ultimately culminating at 89.47% in Cycle II. These outcomes underscore that embedding scrapbook-supported PBL into the classroom operationally elevates student attentiveness, teacher pedagogical proficiency, and conceptual comprehension of IPAS topics. ABSTRAK Penelitian penanganan kelas ini bermaksud guna mendongkrak output belajar, keterampilan guru, dan unjuk kerja peserta didik pada muatan keilmuan IPAS materi Daerahku Kaya Sumber Daya di kelas IV SDN 2 Pelem berbasiskan pengaplikasian model Problem Based Learning (PBL) dibantu media scrapbook. Hal mendasar penelitian ini karena prestasi akademis belajar rendah, dibenarkan oleh persentase tuntasnya pretest sebesar 21,05%. Penelitian dilangsungkan dua siklus dimana mereka melalui tahapan merancang, melaksanakan tindakan, memantau, dan peninjauan ulang berpatokan model Kemmis dan Mc Taggart. Subjek sasaran jumlahnya 19 peserta didik kelas IV. Data dihimpun dengan bantuan tes kinerja belajar, lembaran observasi, wawancara, dan dokumentasi. Hasil penelitian memperlihatkan meningkatnya tuntasnya belajar dari 21,05% pada pratindakan, berubah jadi 63,16% di siklus I, dan meraih 89,47% di siklus II. Peningkatan tersebut membuktikan jika diterapkannya model Problem Based Learning berbantuan media scrapbook mampu meningkatkan keaktifan, keterampilan guru, dan pemahaman peserta didik, terkhusus muatan IPAS secara signifikan.